Revision of the Eocene ‘Platyrhina’ species from the Bolca Lagerstätte (Italy) reveals the first panray (Batomorphii: Zanobatidae) in the fossil record - Marramà, Giuseppe (J Syst Palaeontol, 2020)
The fossil-Lagerstätte of Bolca (Italy) is well known for the diversity and exquisite preservation of its bony and cartilaginous fishes documenting tropical shallow-water marine environments associated with coral reefs in the western Tethys during the early Eocene. In this study, the taxonomic, systematic and phylogenetic position of two batoid species traditionally assigned to the living thornback ray genus Platyrhina is re-evaluated. †Platyrhina bolcensis Heckel, 1851 is recognized as a separate species of the Platyrhinidae because of its plate-like antorbital cartilage with an irregular outline and a small horn on the nasal capsules. Also, the rostral cartilage does not reach the anterior border of the disc. Support for the placement of this species within the new genus †Eoplatyrhina gen. nov. is based on a combination of morphological and meristic features (e.g. nasal capsules at right angles to the rostrum; large space between the hyomandibulae and mandibular arch; approximately 132 vertebral centra; 15–16 rib pairs; 81–87 pectoral radials; 18–21 pelvic radials; short, straight and stout claspers; 40–50 caudal-fin radials; thorns absent). A second species, †Platyrhina egertoni (De Zigno, 1876), is more closely related to the living panray Zanobatus than Platyrhina and is assigned here to †Plesiozanobatus gen. nov. because of a combination of characters that support its placement within the family Zanobatidae (tail stout and short, distinctly demarcated from disc; two dorsal fins and complete caudal fin; small dermal denticles and scattered thorns covering disc and tail; rostral cartilage absent; nasal capsules without horn-like processes; mesopterygium absent). The systematic position of a third taxon, †Platyrhina gigantea (Blainville, 1818), is currently impossible to establish due to the poor preservation of the only known specimen, and therefore we propose to consider it a nomen dubium. Palaeoecological and biogeographic features of the Eocene platyrhinids and zanobatids from Bolca are also discussed. http://zoobank.org/urn:lsid:zoobank.org:pub:B4C7A979-7972-409B-B489-A6DDD5E35FE5